2001
DOI: 10.1212/wnl.57.12.2217
|View full text |Cite
|
Sign up to set email alerts
|

Memory complaints and APOE-ε4 accelerate cognitive decline in cognitively normal elderly

Abstract: Article abstract-Objective: To investigate to what extent subjective memory complaints and APOE-⑀4 allele carriage predict future cognitive decline in cognitively intact elderly persons, by evaluating both their separate and combined effects. Methods: We selected 1,168 subjects from the population-based Longitudinal Aging Study Amsterdam who were 62 to 85 years of age and had no obvious cognitive impairment at baseline (Mini-Mental State Examination [MMSE] score, Ն27). Memory complaints and APOE phenotypes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
155
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(175 citation statements)
references
References 48 publications
12
155
1
4
Order By: Relevance
“…[34][35][36][37][38][39][40][41] The present study recruited individuals without subjective or objective cognitive impairment, hence subjects with normal cognition, to test the effects of APOE4 on the brain functioning of WM by using BOLD fMRI. Performance of n-back WM was not different between groups (P ϭ .41-.85), similar to the findings of a previous publication.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37][38][39][40][41] The present study recruited individuals without subjective or objective cognitive impairment, hence subjects with normal cognition, to test the effects of APOE4 on the brain functioning of WM by using BOLD fMRI. Performance of n-back WM was not different between groups (P ϭ .41-.85), similar to the findings of a previous publication.…”
Section: Discussionmentioning
confidence: 99%
“…However, although a significant number of elderly individuals does not present an objective deficit of memory that can be documented by neuropsychological tests, they very often complain about their mnemonic development in activities of daily living. These individuals comprise a relevant investigative group, as the subjective memory malfunction complaint is capable of anticipating possible dementia processes (2) . Elderly individuals who enjoy a normal cognitive performance, and yet subjectively complain about memory deficit, may develop Alzheimer's disease two years following a clinical followup (3) .…”
Section: Introductionmentioning
confidence: 99%
“…Several longitudinal population-based studies of subjective memory complaints in older adults without dementia have reported an association with future cognitive decline (Dik et al, 2001;Jorm et al, 2001), dementia (Schmand et al, 1997;Palmer et al, 2003;Wang et al, 2004;Kim et al, 2006), AD (van Oijen et al, 2007), and Alzheimer's pathology at autopsy (Barnes et al, 2006). More recent longitudinal studies have excluded participants with both dementia and MCI at baseline, and have reported associations between subjective memory complaints and subsequent cognitive decline (Glodzik-Sobanska et al, 2007) and AD (Heun et al, 2006).…”
Section: Introductionmentioning
confidence: 99%